An efficient catalytic degradation of trichloroethene in a percarbonate system catalyzed by ultra-fine heterogeneous zeolite supported zero valent iron-nickel bimetallic composite - Danish, Muhammad; Gu, Xiaogang; Lu, Shuguang; Brusseau, Mark L.; Ahmad, Ayyaz; Naqvi, Muhammad; Farooq, Usman; Zaman, Waqas Qamar; Fu, Xiaori; Miao, Zhouwei (Applied catalysis. A, General, 2017)
[Display omitted] •A novel ultra-fine natural zeolite supported Fe-Ni composite was synthesized.•The catalytic ability and stability of Z-nZVI-Ni increased significantly.•Z-nZVI-Ni demonstrated remarkable performance for TCE degradation.•The hydroxyl radicals (OH) played the dominant role in TCE degradation.•The slow leaching of Fe and Ni presented its extended stability. Zeolite supported nano iron-nickel bimetallic composite (Z-nZVI-Ni) was prepared using a liquid-phase reduction process. The corresponding surface morphologies and physico-chemical properties of the Z-nZVI-Ni composite were determined using scanning electron microscopy (SEM), transmission electron microscopy (TEM), Energy dispersive X-ray spectra (EDS), Brunauer Emmett Teller (BET) adsorption, wide angle X-ray diffractometry (WA-XRD), and Fourier transform infrared spectroscopy (FTIR). The results indicated high dispersion of iron and nickel nano particles on the zeolite sheet with an enhanced surface area. Complete destruction of trichloroethene (TCE) and efficient removal of total organic carbon (TOC) were observed by using Z-nZVI-Ni as a heterogeneous catalyst for a Fenton-like oxidation process employing sodium percarbonate (SPC) as an oxidant. The electron spin resonance (ESR) of Z-nZVI-Ni verified the generation and intensity of hydroxyl radicals (OH). The quantification of OH elucidated by using p-chlorobenzoic acid, a probe indicator, confirmed the higher intensity of OH. The transformation products were identified using GC–MS. The slow iron and nickel leaching offered higher stability and better catalytic activity of Z-nZVI-Ni, demonstrating its prospective long term applications in groundwater for TCE degradation.